Exploring the Potential of Syzygium cumini (L.) Skeels (Jamun) Seed Powder as an Eco-Friendly Agent for Developing Friction Ridges on Porous and Nonporous Surfaces - Vaibhav Sharma; Abhishek R. Rai; Divyansh Jain; Poonam Kumari; Varad Nagar; Anubhav Singh; Kumud Kant Awasthi; Archana Gautam; Tina Sharma; Mahipal Singh Sankhla; Anuj Sharma (Wolters Kluwer Medknow Publications, 2024)
Background: Development of obscured fingerprints on a diverse range of surfaces is a crucial aspect of forensic investigations. Aims and Objectives: In this particular study, the utilization of Syzygium cumini (L.) Skeels (Jamun) seed powder was examined for the purpose of revealing hidden fingerprints on a variety of surfaces, including both permeable and impermeable substrates. Materials and Methods: The seed powder was extracted using a simple process and was analysed using multiple analytical techniques. The efficacy of the jamun seed powder in developing latent fingerprints was evaluated. Results: The findings of this investigation demonstrate that the jamun seed powder was capable of producing fingerprint patterns of exceptional quality and clarity on numerous surfaces. Conclusion: This research highlights the potential use of jamun seed powder as a practical and effective alternative for the development of hidden fingerprints in forensic investigations, while also providing cost-effectiveness.